Vývoj a súčasné trendy pri príprave nanoštruktúrovaných biosenzorov - Bertók, Tomáš; Šefčovičová, Jana; Gemeiner, Peter; Tkáč, Ján (Chemické listy, 2012)
This review deals with the main characteristics of modern nanostructures like Au nanoparticles or C nanotubes and the great potential of their application in biosensor manufacture. The principles of biosensing are also mentioned, focusing on the label-free electrochemical detection using self-assembled monolayers on Au surfaces. This review deals mostly with biosensors for use in clinical chemistry and diagnostics as immunosensors. Application of nanoparticles can improve electrode transduction although antigens and antibodies do not form a redox couple.
Keywords: nanotechnologie; sekvenční analýza DNA; nanostruktury; Sequence Analysis, DNA; biosenzitivní techniky; Biosensing Techniques; Nanostructures; Nanotechnology; Nanoparticles; nanočástice